Impact of ICT on test results standardized during COVID-19: The performance of students in Colombia and Panama - Mauris De La Ossa, Leonardo Alberto; Domínguez Gil, Blanca Patricia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
According to studies, students who had the mediation of ICTs in their training process during the confinement caused by the pandemic had better results in standardized tests. This investigation, of a documentary nature, investigated the case of Colombia and Panama, finding that the pattern was indeed repeated. With the aggravating circumstance that, in these countries, the percentage of students without access to these resources exceeded more than 50%. Therefore, it is concluded that the learning processes were seriously affected during COVID-19, with damage, which could take a decade to be overcome.